Sosialisasi Pembuatan Jamu Tradisional Dari Tanaman Obat Keluarga (Toga) di Desa Batu Kumbung, Kecamatan Lingsar, Lombok Barat - sofiatunnufus; Agus Pratomi Mulyo; Ananda Rizantia Nurmalia; Anggun Oktaviani; Ayu dahlia; Melia Safirani Fitri; Rani Bahiratun Azizah; Sapena farida; Torikul Azis; Joko Sumarsono; Candra Eka Puspitasari (Universitas Mataram, 2022)
Medicinal plants can be used as a raw material for jamu. Medicinal plants can grow freely anywhere. One of the famous villages with extensive agricultural land and a lot of agricultural products, including abundant local plants, is Batu Kumbung Village. Batu Kumbung Village is one of the villages located in Kecamatan Lingsar, Lombok Barat, West Nusa Tenggara. Most people in Batu Kumbung Village have a lower knowledge about the potential of local plants in this village. The purpose of this socializing is to educate villagers about the potential of local plants to be developed to be herbal medicine. The implementation of this socializing activity consists of three methods such as; 1) observation, 2) socializing, and 3) demonstration of how to make jamu. Based on the socializing activities, so many villagers are enthusiastic about participating in the activity, there are some people interested in using local plants for making jamu, and all of the audience can understand how to make a healthy drink or jamu based on local plants. The end of this socializing, can be concluded that the socializing about how to make jamu based on local plants in Batu Kumbung Village was successful, the villagers were very enthusiastic, and the audience know how to make a healthy drink or Jamu. This socializing is expected to improve the ability of people’s to understand about how the production of medicinal plants in Batu Kumbung Village.